Cicero’s humanitas in forensic Speech: focusing on Pro Roscio Amerino - Ahn, Jaewon (Classica - Revista Brasileira de Estudos Clássicos, 2009)
Many investigations regarding this were already made that the idea humanitas originated directly from Greek New comedy and especially from philosophy of Plato and the Stoics but fundamentally from the Greek literatures like those of Homer. Regarding to this, however, the real birth and growth place of the idea of humanitas and the sub-ideas was not classroom but forum in which legal court or political assembly was held. The most significant evidences for this are Cicero’s speeches, because it is not difficult to discover the fact that Cicero’s speeches are usually disposed according to the idea of humanitas and are full of sub-ideas of it. As an exmaple for this, I have tried to analyze Cicero’s Pro Roscio Amerino which is the first causa publica for Cicero. Based on this, I would like to suggest that Cicero’s speeches are to be emphasized also in the humanitas-studies. To this, it should be mentioned that there are some strong relationships between Cicero’s speeches and his late theoretical texts. Thus, philologically seen, my concrete suggestion in this paper is to investigate the so-called ‘intertextuality-problem’ between Cicero’s speeches and philosophical treatises.